The cost of doing business abroad and international capital market equilibrium - Milind Shrikhande (Federal Reserve Bank of Atlanta, 1997)
The implications of the costs of doing business in foreign countries for the resulting capital market equilibrium are studied. When transferring capital goods across national boundaries, the costs incurred are quasi-fixed in a one-good, two-country, intertemporal model with complete financial markets. In our model of the international capital market, deviations from purchasing power parity are endogenously generated. The relative price of physical resources located in one country compared to resources located in another is called the "real exchange rate." The outcome of the model-based analysis is an endogenous generation of a mean-reverting real exchange rate in a continuous-time, general equilibrium model of the international capital market. In dynamic equilibrium, the transfer of capital goods between the two countries is found to be infrequent and lumpy in nature as is observed in foreign direct investment.
Keywords: 330; Capital market; International finance; Macroeconomics